2016
DOI: 10.21767/2471-982x.100014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Medicinal Cannabis Therapy (MCT) on Severity of Chronic Low Back Pain, Sciatica and Lumbar Range of Motion

Abstract: Background: Anecdotal evidence indicates the possible efficacy of cannabis use as an adjunctive treatment in chronic low back pain. The purpose of the current study was to assess the results of treatment of patients suffering from chronic low back pain by medicinal cannabis (MCT). Methods: A cohort of 46 patients was followed for a minimum of twelve months. They were evaluated at baseline prior to MCT, 3 months later when MCT was begun and up to 12 months of MCT by patient reported outcome questionnaire (SF-12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 8 publications
3
23
1
Order By: Relevance
“…Of interest is our findings regarding the reduction in consuming all types of analgesic medications, which further supports earlier reports of analgesics sparing effect of MC treatment (Bradford et al., 2018; Haroutounian et al., 2016; McCarty, 2018; Stith et al., 2017; Yassin et al., 2016). In light of the ‘opioid epidemic’ (Fitzcharles & Eisenberg, 2018), reduction in opioids consumption and even cessation of their use is an important goal.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Of interest is our findings regarding the reduction in consuming all types of analgesic medications, which further supports earlier reports of analgesics sparing effect of MC treatment (Bradford et al., 2018; Haroutounian et al., 2016; McCarty, 2018; Stith et al., 2017; Yassin et al., 2016). In light of the ‘opioid epidemic’ (Fitzcharles & Eisenberg, 2018), reduction in opioids consumption and even cessation of their use is an important goal.…”
Section: Discussionsupporting
confidence: 90%
“…Third, the fact that only 50% of the patients who completed the baseline questionnaires were included in the long‐term analyses may affect generalization of findings and the determination of responder profile. However, a high unaccounted dropout rate is an inherent shortcoming of all such cohort studies (Abuhasira et al., 2018; Haroutounian et al., 2016; Yassin et al., 2016; Zaki et al., 2017). Forth, higher baseline pain intensities than typically seen in other studies (Portenoy et al., 2007) were reported by our patients (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing evidence that MC treatment has opioid-sparing effects [36][37][38][39][40]. Here, we found that responders to MC treatment also reported lower rates of consumption of opioids and triptans compared to non-responders.…”
Section: Discussionmentioning
confidence: 45%
“…However, the study cited by Häuser and Fitzcharles was published after the predefined date for trials inclusion (July 2015). Furthermore, we would like to note that long term benefits have recently been published, and although not from randomized controlled trials (RCT), for long term follow-up of 6 months to one year, showing significant improvement of chronic pain and associated symptoms by medical cannabis inhalation (16)(17)(18) and similarly in 9 months follow-up of tetrahydrocannabinol/cannabidiol (THC/CBD) spray treatment (19). We agree that future meta-analyses should include analyses for very short/short/intermediate/ long trials duration.…”
mentioning
confidence: 99%